High-risk human papillomaviruses distribution in Romanian women with negative cytology - Plesa, Adriana; Socolov, Demetra; Huica, Irina; Botezatu, Anca; Iancu, Iulia Virginia; Ungureanu, Carmen; Teleman, Sergiu; Albulescu, Adrian; Fudulu, Alina; Anton, Gabriela (The Journal of Infection in Developing Countries, 2019)
Introduction: Romania has the highest incidence and mortality rate of cervical cancer in Europe. The objective was to estimate the prevalence of high-risk human papillomavirus (hrHPV) genotypes and to evaluate the role of certain socio-behavioral factors in acquiring viral infection, in a cohort of Romanian women with negative Pap. Methodology: In a prevalence study 611 women (aged 17-58 years) with negative Pap, with no known history of atypical cytology and valid HPV test were included. Each participant completed a questionnaire containing data on socio-behavioral factors. From 344 women aged between 30-58 years, 63 were randomly selected for a second examination (conventional cytology and HPV detection and genotyping) after twelve months. Results: Of the 611 women, 19.80% were HPV positive, 14.73% infected with hrHPV. Differences in the prevalence of hrHPV (17.60% versus 12.50%) as single (13.01% vs 9.01%) and multiple infections (9.71% vs 3.49%) were noted between women under the age of 30 and above. Among socio-behavioral factors, marital status and multiple sexual partners correlate with HPV and hrHPV infection. At follow-up, from 34 HPV negative cases, 10 changed to positive (5 hrHPV), while 2 developed abnormal cytology. Out of the 29 HPV positive cases, 12 cleared the HPV infection and 17 retested positive of which 4 worsened their cytology. Conclusions: In Romania, HPV infection is common in women with negative cytology. HPV genotyping is of epidemiological importance because the distribution of hrHPV types can determine the impact of prophylactic vaccines and the necessity of HPV testing as screening method.